Questionnaire-Related Deferrals in Regular Blood Donors in Norway. (17th January 2012) - Reikvam, Håkon; Svendheim, Kjersti; Røsvik, Anne S.; Hervig, Tor
Abstract : Voluntary donation is a key issue in transfusion medicine. To ensure the safety of blood transfusions, careful donor selection is important. Although new approaches to blood safety have dramatically reduced the risks for infectious contamination of blood components, the quality and the availability of blood components depend on the willingness to donate and the reliability of the information given by the donors about their own health, including risk behavior. As donors who are deferred by the blood bank will be less motivated to return for donation, it is important to reduce the number of deferrals. The aims of the present study were to investigate the reasons for deferral of registered donors coming to the blood bank for donation, in order to identify areas of importance for donor education—as these deferrals potentially could be avoided by better donor comprehension. Deferral related to testing of donors is not included in this study as these deferrals are dependent on laboratory results and cannot be indentified by questionnaire or interview. Data were collected from all blood donors in a period for 18 months who came for blood donation at a large university hospital in Norway. 1 163 of the 29 787 regular donors, who showed up for donation, were deferred (3.9%). The main reasons were intercurrent illness (n = 182 ) (15.6%), skin ulcers (n = 170 ) (14.6%), and risk behaviour (n = 127 ) (10.9%). In a community, intercurrent illnesses, skin ulcers, and potential risk behavior are the most frequent reasons for deferral of regular donors. Strategized effort on donor education is needed, as "failure to donate" reduces donor motivation.